ANALYSIS OF THE INITIAL DEVELOPMENT OF WATERMELON SEEDS (Citrullus lanatus) WITH DIFFERENT CONCENTRATIONS OF GIBBERELLIC ACID: Influence on Germination Time and Root Growth (REMUNOM, 2025)
Watermelon (Citrullus lanatus) is one of the main crops of the Cucurbitaceae family, with high economic and nutritional importance. However, it presents germination challenges that can be mitigated by the use of growth regulators such as gibberellic acid (GA₃). This study aimed to evaluate the influence of different GA₃ concentrations on seed germination and early seedling development of watermelon. The experiment was carried out in a completely randomized design with four treatments: control, 75% (0,937 g/1/2L), 100% 1,25 g/1/2L) and 200% (2,5 g/1/2L) GA₃. Seeds were subjected to a germination test and subsequently transplanted into soil to assess shoot and root growth. Results indicated that the ideal dose (100%) provided the highest germination rate (96%), while the minimum dose (75%) showed the best shoot growth after 15 days (13.5 cm). In contrast, the control treatment showed the greatest root growth (5.9 cm), whereas the maximum dose (200%) was the most detrimental, suggesting a physiological resource allocation toward shoot elongation. It is concluded that GA₃ positively influences germination and shoot development; however, excessive doses compromise root system formation, highlighting the need to define an adequate concentration to ensure balanced seedling growth.